2022
DOI: 10.1186/s40850-022-00148-3
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary morphology of sperm in pholcid spiders (Pholcidae, Synspermiata)

Abstract: Background Pholcidae represent one of the largest and most diverse spider families and have been subject to various studies regarding behavior and reproductive biology. In contrast to the solid knowledge on phylogeny and general reproductive morphology, the primary male reproductive system is strongly understudied, as it has been addressed only for few species. Those studies however suggested a high diversity of sperm and seminal secretions across the family. To address this disparity and recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Huber et al 2018). The monophyly of this northern clade suggests that cleistospermia have evolved at least twice in Pholcidae: once in the ancestor of Pholcophora and Tolteca (Dederichs et al 2022), and once in all Pholcidae except Ninetinae. The sperm transfer form of Papiamenta is unknown but our results generate the prediction that Papiamenta males also transfer cleistospermia.…”
Section: Relationshipsmentioning
confidence: 94%
See 1 more Smart Citation
“…Huber et al 2018). The monophyly of this northern clade suggests that cleistospermia have evolved at least twice in Pholcidae: once in the ancestor of Pholcophora and Tolteca (Dederichs et al 2022), and once in all Pholcidae except Ninetinae. The sperm transfer form of Papiamenta is unknown but our results generate the prediction that Papiamenta males also transfer cleistospermia.…”
Section: Relationshipsmentioning
confidence: 94%
“…The most comprehensive phylogeny of Pholcidae (Eberle et al 2018) recognized a "North and Central American and Caribbean" clade of Ninetinae, but the species sample was small (four species, of which two could not confidently be assigned to a genus) and lacked the genus Tolteca. A recent comparative study of pholcid sperm ultrastructure (Dederichs et al 2022) found that Pholcophora and Tolteca share cleistospermia while all other studied Ninetinae have synspermia; since synspermia are thought to be plesiomorphic for Pholcidae, this was a first indication that Pholcophora and Tolteca might be closely related.…”
Section: Introductionmentioning
confidence: 96%
“…Three of these have been subject to detailed studies regarding copulatory mechanics so far: Pholcinae [ 35 , 36 , 38 , 39 ], Smeringopinae [ 34 , 35 ] and Modisiminae [ 10 , 37 ], leaving Arteminae and Ninetinae understudied in this regard. Ninetines are particular as previous studies on the primary male reproductive system reveal the presence of synspermia (aggregation of fused spermatozoa; [ 41 , 42 ]) instead of cleistosperm as in other pholcids, and a remarkable variation in the female genital system [ 29 ], with, however, very little to no available data on their reproductive biology so far. Furthermore, Ninetinae has been suggested to occupy a ‘basal' position in the pholcid phylogeny [ 31 ], which makes them highly suitable for studies on the evolution of pholcid spiders.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular data later suggested instead an affinity either with Modisiminae (Bruvo-Mađarić et al 2005;Eberle et al 2018) or with Modisiminae + Arteminae (Eberle et al 2018). Recent data on sperm ultrastructure also found similarities between Priscula and certain Modisiminae (Dederichs et al 2022). Such an affinity makes sense geographically, as both Priscula and Modisiminae are restricted to the New World.…”
Section: Introductionmentioning
confidence: 99%